2015
DOI: 10.1016/j.devcel.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebral Cavernous Malformation Pathway Controls Cardiac Development via Regulation of Endocardial MEKK3 Signaling and KLF Expression

Abstract: SUMMARY The cerebral cavernous malformation (CCM) pathway is required in endothelial cells for normal cardiovascular development and to prevent postnatal vascular malformations, but its molecular effectors are not well defined. Here we show that loss of CCM signaling in endocardial cells results in mid-gestation heart failure associated with premature degradation of cardiac jelly. CCM deficiency dramatically alters endocardial and endothelial gene expression, including increased expression of the Klf2 and Klf4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
205
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(215 citation statements)
references
References 63 publications
8
205
0
Order By: Relevance
“…The severe endocardial defects and loss of endocardial cushion formation in CCM mutants can be explained by an earlier finding that the inhibition of Notch signalling causes increased Bmp6 expression; this, in turn, triggers pathological endMT (Maddaluno et al, 2013). It was recently shown that the loss of CCM proteins in mice activates the mitogen-activated protein kinase kinase kinase 3 (Map3k3; also known as Mekk3) signalling pathway, resulting in increased expression of ADAM metallopeptidase with thrombospondin type 1 motif 4/5 (Adamts4/5) proteases, which degrade cardiac jelly, and increased levels of Klf2 (Zhou et al, 2015). Furthermore, it was found that the endocardial CCM mutant phenotypes in zebrafish are the result of the overexpression of Klf2a and Klf2b, which are activated by β1 integrin in a blood flow-independent manner (Renz et al, 2015).…”
Section: Mechanosensitive Pathways Within the Endocardiummentioning
confidence: 99%
See 3 more Smart Citations
“…The severe endocardial defects and loss of endocardial cushion formation in CCM mutants can be explained by an earlier finding that the inhibition of Notch signalling causes increased Bmp6 expression; this, in turn, triggers pathological endMT (Maddaluno et al, 2013). It was recently shown that the loss of CCM proteins in mice activates the mitogen-activated protein kinase kinase kinase 3 (Map3k3; also known as Mekk3) signalling pathway, resulting in increased expression of ADAM metallopeptidase with thrombospondin type 1 motif 4/5 (Adamts4/5) proteases, which degrade cardiac jelly, and increased levels of Klf2 (Zhou et al, 2015). Furthermore, it was found that the endocardial CCM mutant phenotypes in zebrafish are the result of the overexpression of Klf2a and Klf2b, which are activated by β1 integrin in a blood flow-independent manner (Renz et al, 2015).…”
Section: Mechanosensitive Pathways Within the Endocardiummentioning
confidence: 99%
“…Klf2 expression is also controlled by the cerebral cavernous malformations (CCM) complex in mice and zebrafish (Renz et al, 2015;Zhou et al, 2015). CCM complex components play a role in controlling the response of β1 integrin signalling to blood flow in endothelial cells (Macek Jilkova et al, 2014), and the loss of CCM proteins in mouse and zebrafish results in severe cardiovascular defects (Boulday et al, 2009;Hogan et al, 2008;Kleaveland et al, 2009;Mably et al, 2003Mably et al, , 2006Renz et al, 2015;Yoruk et al, 2012;Zheng et al, 2010;Zhou et al, 2015).…”
Section: Mechanosensitive Pathways Within the Endocardiummentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies have demonstrated that shear stress11 along with small molecules such as lipid‐lowering statins10, 12 and resveratrol are capable of exerting vasoprotective effects by promoting KLF2 activation 4, 12, 13. The molecular mechanisms involved in the regulation of endothelial KLF2 expression includes the AMP‐activated protein kinase/dual specificity mitogen‐activated protein kinase kinase 5/extracellular‐signal related kinase 5/MEF2 (myocyte enhancing factor 2) pathway and the histone deacetylase (HDAC) 5 pathway 1, 14, 15. Recent studies have demonstrated that deletion of 1 KLF2 allele in mice increases atherosclerosis,16 and KLF2 controls endothelial and vascular integrity 17.…”
mentioning
confidence: 99%